2021
DOI: 10.4236/ojic.2021.111002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Activities of Binuclear Metal Complexes of 2-Benzoylpyridine and Phenyl(Pyridin-2-yl) Methanediol Derived from 1-Phenyl-1-(Pyridin-2-yl)-N-(Pyrimidin-2-yl) Methanimine Dihydrate Schiff Base

Abstract: The Schiff base, 1-phenyl-1-(pyridin-2-yl)-N-(pyrimidin-2-yl)methanimine dihydrate (L 1 ) has been synthesized by the condensation reaction between 2-aminopyrimidine and 2-benzoylpyridine and characterized using 13 C-NMR, 1 H-NMR, microanalysis, FT-IR, DEPT-135, HSQC, HMBC, COZY, NOESY. The reaction of 1-phenyl-1-(pyridin-2-yl)-N-(pyrimidin-2-yl)methanimine dihydrate (L 1 ) with salts of V(IV), Co(II) and Cu(II), however, resulted in the hydrolysis of L 1 to give binuclear metal complexes of 2-benzoylpyridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The binuclear complexes of the schiff base with transition metal ions V(IV), Co (II) and Cu (II) were obtained and examined for their antibacterial properties against three bacterial strains Escherichia coli, Klebseilla pneumonia and Staphylococcus aureus. The antifungal activity was also determined against three fungal strains Candida albicans, Candida glabrata and Candida parapsilosis.It was revealed that the schiff base showed good to moderate antibacterial and antifungal activities [53].…”
Section: Role Of Schiff Bases As Bioactive Ligandmentioning
confidence: 99%
“…The binuclear complexes of the schiff base with transition metal ions V(IV), Co (II) and Cu (II) were obtained and examined for their antibacterial properties against three bacterial strains Escherichia coli, Klebseilla pneumonia and Staphylococcus aureus. The antifungal activity was also determined against three fungal strains Candida albicans, Candida glabrata and Candida parapsilosis.It was revealed that the schiff base showed good to moderate antibacterial and antifungal activities [53].…”
Section: Role Of Schiff Bases As Bioactive Ligandmentioning
confidence: 99%